Design and descriptive data of the randomized Clubfoot Foot Abduction Brace Length of Treatment Study (FAB24). Issue 2 (March 2017) - Dobbs, Matthew B.; Frick, Steven L.; Mosca, Vincent S.; Raney, Ellen; VanBosse, Harold J.; Lerman, Joel A.; Talwalkar, Vishwas R.; Steger-May, Karen; Gurnett, Christina A.
Abstract : The aim of this study was to describe the design and baseline characteristics of participants enrolled in the prospective randomized-controlled Clubfoot Foot Abduction Brace Length of Treatment Study (FAB24). Foot abduction bracing is currently the standard of care for preventing clubfoot relapse. Current recommendations include full-time bracing for the first 3 months and then 8–12 h a day for 4 years; however, the optimal length of bracing is not known. The FAB24 trial is a clinical randomized study to determine the effectiveness of 2- versus 4-year foot abduction bracing. Participant enrollment for FAB24 was conducted at eight sites in North America and included enrollment and randomization of 139 participants with isolated clubfoot. This clinical trial will generate evidence-based data that will inform and improve patient care.